Analysis of 2-dimensional regional differences in the peripapillary scleral fibroblast cytoskeleton of normotensive and hypertensive mouse eyes - Ann Mozzer; Joe Gerald Jesu Raj; Nushrat Yasmin; Edward Esposito; Ian Pitha (Scientific Reports)
Abstract These studies aimed to study the mechanisms of glaucomatous peripapillary scleral (PPS) remodeling by investigating IOP-induced changes in fibroblast actin-collagen alignment and nuclear morphology in mouse PPS. Cryosections from the optic nerve heads (ONH) of eyes isolated 1- and 6-weeks after bead-induced IOP elevation were imaged for nuclei, fibrillar actin (FA), and collagen (second harmonic generation, SHG). Two-dimensional nuclear morphology was analyzed using VAMPIRE machine-learning image analysis and FA-collagen alignment was determined by comparing vector fields of FA and SHG images. Nuclear morphology was regionally defined with the internal (pial) PPS (iPPS) containing nuclei with higher aspect ratios than the peripheral PPS (outer PPS, oPPS) and peripheral sclera. FA-collagen alignment was higher in the PPS than in the peripheral sclera (7.1 ± 2.5° versus 10.0 ± 1.4°, p = 0.05, n = 6). One and six weeks after BI, there were non-significant nuclear morphologic changes reflecting a transition to a rounder shape in all scleral regions and persistently reduced FA-collagen alignment in the PPS regions. This study therefore concludes that chronic IOP elevation is associated with persistent alterations in FA-collagen alignment that indicate sustained cellular responses to tissue stress.